2008
DOI: 10.1167/iovs.07-0847
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Posterior Polymorphous Corneal Dystrophy 3 Gene,TCF8, in Late-Onset Fuchs Endothelial Corneal Dystrophy

Abstract: The identification of a novel missense mutation in only one of the patients implied that TCF8 does not play a significant role in the pathogenesis of FECD in this Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 30 publications
0
49
2
Order By: Relevance
“…6 Mutations in the ZEB1 (zinc-finger E-box binding homoebox 1) gene can cause both sporadic and familial late-onset FED. 6,14 ZEB1 is expressed in the CE. 15 It regulates cell proliferation and differentiation by inducing epithelial-mesenchymal transition.…”
Section: Introductionmentioning
confidence: 99%
“…6 Mutations in the ZEB1 (zinc-finger E-box binding homoebox 1) gene can cause both sporadic and familial late-onset FED. 6,14 ZEB1 is expressed in the CE. 15 It regulates cell proliferation and differentiation by inducing epithelial-mesenchymal transition.…”
Section: Introductionmentioning
confidence: 99%
“…Late-onset classic FECD can either be familial or sporadic, with an onset typically occurring after the age of 40 years. Although mutations in the zinc-finger E-box binding homeobox 1 (ZEB1) gene 6,7 and the solute carrier family 4 member 11 (SLC4A11) gene 8,9 have been reported as causative of late-onset FECD, these mutations were only rarely observed in the patient population. On the other hand, Baratz et al 10 reported that a genome-wide association study (GWAS) revealed a highly significant association between single nucleotide polymorphisms in transcription factor 4 genes (TCF4) in classic late-onset FECD.…”
mentioning
confidence: 99%
“…Other candidates tested include the TCF8/ZEB1 (PPCD3) gene and the COL8A1 (collagen VIII, alpha-1 chain) gene. No significant role was found for either of these genes in FECD (Urquhart et al 2006;Mehta et al 2008;Vithana et al 2008). …”
Section: Genetics Of Fecdmentioning
confidence: 86%